2020
DOI: 10.4314/jae.v24i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of bio-security measures against avian-influenza outbreaks among poultry farmers in Jigawa State, Nigeria

Abstract: The study examined the adoption of selected bio-security measures against avian-influenza (HPAI-A/H5N1) outbreaks among poultry farmers in Jigawa State, Nigeria. A total of 120 respondents selected through a multistage sampling procedure was used for the study. Structured questionnaire was used to elicit information from the respondents. Data collected were subjected to percentages, mean and binary regression. The study revealed that the high level of adoption on biosecurity measures of segregation and traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…while lack of steady/sustainable market (𝑥̅ = 2.625), lack of manpower to implement biosecurity (𝑥̅ = 2.633) and incompatibility of the biosecurity measures with socio-cultural background of the farmers were not seen as severe constraints to the respondents. This is in line with the submission of Oladipo et al (2020) that the major constraints of poultry farmers on biosecurity practices is literacy level among others.…”
Section: Constraints Of the Youth Farmers To Adoption Of Biosafety Pr...supporting
confidence: 83%
“…while lack of steady/sustainable market (𝑥̅ = 2.625), lack of manpower to implement biosecurity (𝑥̅ = 2.633) and incompatibility of the biosecurity measures with socio-cultural background of the farmers were not seen as severe constraints to the respondents. This is in line with the submission of Oladipo et al (2020) that the major constraints of poultry farmers on biosecurity practices is literacy level among others.…”
Section: Constraints Of the Youth Farmers To Adoption Of Biosafety Pr...supporting
confidence: 83%
“…Lack of veterinary extension services can have negative effects on poultry management. For instance, in another study, the absence of veterinary support personnel was found to be significantly related to a lower rate of adoption of biosecurity measures by poultry farmers in northern Nigeria [25].…”
Section: Access To Veterinary Servicesmentioning
confidence: 97%